From Patriarchy to Intersectionality: A Transnational Feminist Assessment of How Far We've Really Come - Patil, Vrushali (The University of Chicago, 2013)
This article examines the general shift in feminist scholarship from the use of the concept of patriarchy to the concept of intersectionality from a transnational feminist perspective. It first reviews some central critiques of patriarchy (the problems of unidimensionality, universality, and tautology) and then examines intersectional scholarship that emerged in response. Reviewing research applications of intersectionality since the year 2000, it argues that these applications constitute an incomplete shift from the concept of patriarchy. That is, it argues that unrecognized problems with the concept of patriarchy continue to haunt contemporary intersectional applications. Specifically, intersectional scholarship tends to suffer from the ongoing legacy of patriarchy’s reification of nation-state borders and its failure to interrogate the significance of cross-border processes for shaping gender relations and identities. Next, in contrast to such conceptualizations of patriarchy, this article examines the empirically specific classic and modern patriarchies of early modern and modern Europe. In doing so, it demonstrates the cross-border dimensions of these patriarchies, particularly their importance for imperial and colonial processes. It also discusses contemporary patriarchies in the anticolonial and postcolonial world in similar transnational perspective. It argues that many of the patriarchies that are today discussed as domestic patriarchies—often in quite complex ways, via the language of intersectionality—are actually embedded within deep transnational histories that must be recognized and interrogated.